'Mértola, a lab for the future' as a transformational plan for the mediterranean semi-arid region: A learning case based on landsenses ecology. Issue 7 (3rd October 2021) - Cortegano, Marta; Dias, Ricardo Cunha; Guedes Vidal, Diogo; Seixas, Paulo Castro
ABSTRACT: Learning cases as Transformational Plans are a tool that is still little explored and that have great potential in the framework of Landsenses Ecology as an emerging discipline. This work presents the project 'Mértola, a Lab for the Future' as a learning case of a Transformational Plan in the Mediterranean semi-arid region based on Landsenses Ecology. It is a project of agroecological transition, adaptation to climate change and desertification combat that places the local community leadership in the planning of a more sustainable and resilient future. The paper proposes Transformational Plans as a tool to promote networks for the sharing of technical-scientific, political and practical/lay knowledge enhancing a people-centred and place-based change. The learning case methodology follows an analysis showing a set of good governance practices for sustainability, through six transformation domains: access to natural ecosystems, knowledge and culture, systems of exchange, networks, equity, and discourse. Results show a strong articulation between the learning case and the UN 2030 Agenda, highlighting SDGs location and territorialization practices. This kind of projects, which strongly connects with governance and its multilevel and territorial translation, have a great potential for the Landsenses Ecology, contributing to innovate in governance approaches. The same place-based approach could be used and replicated by other territories in the Mediterranean semi-arid region to develop their Transformational Plans for accelerating transformation towards more sustainable territories.